2006
DOI: 10.1016/j.cell.2006.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Otoferlin, Defective in a Human Deafness Form, Is Essential for Exocytosis at the Auditory Ribbon Synapse

Abstract: The auditory inner hair cell (IHC) ribbon synapse operates with an exceptional temporal precision and maintains a high level of neurotransmitter release. However, the molecular mechanisms underlying IHC synaptic exocytosis are largely unknown. We studied otoferlin, a predicted C2-domain transmembrane protein, which is defective in a recessive form of human deafness. We show that otoferlin expression in the hair cells correlates with afferent synaptogenesis and find that otoferlin localizes to ribbon-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

46
753
10
13

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 607 publications
(856 citation statements)
references
References 73 publications
46
753
10
13
Order By: Relevance
“…As a single synaptic vesicle contains Ϸ15 synaptotagmin molecules (35), the formation of heterooligomeric assemblies may be an additional complication. Finally, we cannot exclude that an entirely different protein triggers release at the BC-GC synapse in knockout mice, as recently suggested for auditory hair cells (36) and the calyx of Held (37).…”
Section: Discussionmentioning
confidence: 71%
“…As a single synaptic vesicle contains Ϸ15 synaptotagmin molecules (35), the formation of heterooligomeric assemblies may be an additional complication. Finally, we cannot exclude that an entirely different protein triggers release at the BC-GC synapse in knockout mice, as recently suggested for auditory hair cells (36) and the calyx of Held (37).…”
Section: Discussionmentioning
confidence: 71%
“…These mice also have functional afferent neurons, suggesting that otoferlin's role in the auditory pathway lies within the hair cell between the mechanoelectrical transduction and afferent neuron activation steps. In support of this idea, hair cells in otoferlin knockout mice do not release neurotransmitter in response to membrane depolarization and calcium influx, despite having apparently normal synapse morphology (Roux et al, 2006). O toferlin is a large multi-C2 domain protein pro posed to act as a calcium sensor that regulates synaptic vesicle exocytosis in cochlear hair cells.…”
Section: Introductionmentioning
confidence: 83%
“…The IHC synaptic machinery differs from conventional synapses. For example, IHC synapses lack synaptotagmins I-III 1 and complexins 2,3 , but express the ribbon-protein RIBEYE 4 and the multi-C 2 -domain protein otoferlin 5 . Previous studies indicated that the neuronal SNAREs (SNAP [Soluble NSF…”
Section: Snare Proteins Mediate Membrane Fusion Neurosecretion Depenmentioning
confidence: 99%